2018
DOI: 10.1101/427385
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic variability and potential effects on clinical trial outcomes: perspectives in Parkinson’s disease

Abstract: BackgroundImproper randomization in clinical trials can result in the failure of the trial to meet its primary end-point. The last ~10 years have revealed that common and rare genetic variants are an important disease factor and sometimes account for a substantial portion of disease risk variance. However, the burden of common genetic risk variants is not often considered in the randomization of clinical trials and can therefore lead to additional unwanted variance between trial arms. We simulated clinical tri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

6
3

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…Previously, we have shown that active randomization on genetic components of PD is important for successful clinical trials because unbalanced genetic risk may lead to the heterogeneity of intervention arms and lower the power of that trial. 22 Our results suggest that actively balancing PRS is similarly important for a disease modifying/preventing trial targeting p.G2019S carriers.…”
Section: Discussionmentioning
confidence: 72%
“…Previously, we have shown that active randomization on genetic components of PD is important for successful clinical trials because unbalanced genetic risk may lead to the heterogeneity of intervention arms and lower the power of that trial. 22 Our results suggest that actively balancing PRS is similarly important for a disease modifying/preventing trial targeting p.G2019S carriers.…”
Section: Discussionmentioning
confidence: 72%
“…Pre-trial genetic analysis could assist in identifying those at higher risk for developing PD or LBD outside of the risk accounted for at the GBA target. Therefore, future clinical trials involving GBA carriers should include a comprehensive genetic assessment prior to enrolment, as we have previously suggested (Leonard et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…More common variants include p.E326K, p.T369M, p.N370S and p.L444P, whose frequencies vary with ethnicity and are each found on different haplotypes (Blauwendraat et al 2018b;Leija-Salazar et al 2019 In recent years, GBA has become a prominent target for therapeutic development, and the first gene-specific phase 2 clinical trial in PD is currently ongoing for GBA-positive PD patients (ClinicalTrials.gov Identifier: NCT02906020). One of the concerns in performing such a trial is that, despite the randomization for treatment and placebo groups, these groups will remain unbalanced in terms of factors that affect their progression, which can be a significant confounder of trial outcome (Leonard et al 2018). In addition, it is likely that future preventive clinical trials will also target populations that are at high risk for Lewy body diseases, such as GBA risk variant carriers with prodromal symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, predicting rate of progression will be important in balancing treatment/placebo arms in therapeutic trials and may reduce sample sizes needed in future clinical trials. We have modelled the effects of genetic bias in treatment arms in clinical trials [46]. A further initiative is to collate genetic resources from ongoing drug trials to leverage high quality longitudinal data form clinical trials and to enable the study of genetic determinants of drug response and side effects.…”
Section: Advanced Cohort Buildingmentioning
confidence: 99%